2022
DOI: 10.1111/dewb.12345
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and practices arising during public health emergencies: A qualitative survey on ethics committees

Abstract: The particular dynamics of public health emergencies urge scientists and Ethics Committee (EC) members to change and adapt their operating procedures to function effectively. Despite having previous pandemic experiences, ethics committees were unprepared to adapt to COVID-19 pandemic challenges. This survey aims to learn and thoroughly discuss the most salient issues for ECs during the COVID-19 pandemic. The results indicate that the main problems faced by ECs were lack of/insufficient regulations, lack of dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
(10 reference statements)
0
5
0
2
Order By: Relevance
“…However, a study among EC members in China 13 recorded that although the risks were perceived to be potentially more to the individual participants, the long-term benefits to the society at large were considered greater. Although the pressure for issuance of quick approvals was felt and expressed as a need of the pandemic time, it was not perceived as political pressure as reported in the investigations conducted in other countries 14 15 .…”
Section: Discussionmentioning
confidence: 97%
“…However, a study among EC members in China 13 recorded that although the risks were perceived to be potentially more to the individual participants, the long-term benefits to the society at large were considered greater. Although the pressure for issuance of quick approvals was felt and expressed as a need of the pandemic time, it was not perceived as political pressure as reported in the investigations conducted in other countries 14 15 .…”
Section: Discussionmentioning
confidence: 97%
“…Several of these contributions focus exclusively on one ERC, usually associated with an academic or health care institution. The literature includes descriptions of ERC operations during the pandemic in Central America and the Dominican Republic [17], China [18], Ecuador [19], Egypt [20], Germany [21], India [2224], Iran [10], Ireland [25], Kenya [26], Kyrgyzstan [27], Latin America [28], the Netherlands [29], Pakistan [30], South Africa [31,32], Turkey [33], and the United States [3436]. Most of these studies reported results from surveys, interviews, focus groups, and documentary analysis, including review of research protocols, ERC meeting minutes, and existing SOPs.…”
Section: Discussionmentioning
confidence: 99%
“…El trabajo de los comités de ética, tanto de investigación como de asistencia, se vio entorpecido por las incertidumbres, la falta de precedentes y la desorientación frente a dificultades de recursos materiales y humanos 22 . Primeros estudios empíricos confirman la disposición a aplicar evaluaciones rigurosamente médicas en situaciones de emergencia pandémica, a pesar de que en toda otra situación priman valores relevados por la bioética y los criterios personales de los cuidadores, sobre lo cual será necesario reflexionar una vez superada la urgencia actual, pues todos los criterios valóricos tienden a discriminar contra los desfavorecidos.…”
Section: Atualizaçãounclassified